Possibilities of transposition of the extensores carpi tendons in the treatment of the rheumatoid hand - A. V. Rozov; E. I. Byalik; A. M. Lila (Современная ревматология, 2024)
With the advent of more effective conservative methods of treating rheumatoid arthritis (RA), patients with severe hand deformities are being treated less and less by orthopaedic surgeons. However, when significant changes occur in the hand joints, surgery is the only method to restore their function. The previously widespread arthrodesis procedures are gradually giving way to modern soft tissue joint-preserving surgeries that prevent the development of severe deformities and preserve hand function.Objective: to compare the functional outcomes of extensor carpi ulnaris and extensor carpi radialis longus transposition surgery (ECU+ECRL) and wrist joint arthrodesis in patients with RA.Material and methods. The study included 58 patients with a confirmed diagnosis of RA. Most patients (93%) were women with a disease duration of 4 to 6 years, the mean age was 46.3±14.6 years. All patients were seropositive for rheumatoid factors, most had radiological stages III and IV of RA according to Steinbrocker, radiological stage IV according to Larsen. Most of the patients had moderate disease activity. From 2021 to 2023, 21 patients underwent ECU + ECRL surgery and 37 patients underwent arthrodesis of the wrist joint. The groups were comparable in terms of key clinical characteristics. The average follow-up time after surgery was 6 months.Results and discussion. The mean DASH score in the transposition group (ECU + ECRL) was 38.3±10.12, while in the arthrodesis group it was 47.45±16.92 (p <0.05). In the late postoperative period (after 6 months), all patients showed a positive dynamics according to the visual analogue scale, which was comparable in both groups: in the ECU + ECRL group – 2.66±1.49 cm, in the arthrodesis group – 3.0±1.6 cm. The range of motion of the wrist was significantly greater in the ECU + ECRL group than in the arthrodesis group (p <0.05). At the follow-up examination in the postoperative period, a significant improvement in quality of life according to the EQ-5D was found in both the ECU+ECRL group (0.686) and the arthrodesis group (0.625), p<0.05.Conclusion. X-shaped extensor tendon plastic surgery for wrist joint stabilization should be considered a promising technique that can reduce pain and improve patients' functional status and quality of life.